Bronchial Asthma and Bronchial Hyperresponsiveness and Their Characteristics in Patients with Common Variable Immunodeficiency - Milota, Tomas; Bloomfield, Marketa; Parackova, Zuzana; Sediva, Anna; Bartunkova, Jirina; Horvath, Rudolf (International archives of allergy and immunology, 2019)
BACKGROUND: Common variable immunodeficiency (CVID) is one of the most frequent primary immunodeficiencies and is characterized by disturbed immunoglobulin production and dysregulation of the immune system. Results of previous studies suggest a higher prevalence of bronchial asthma (BA) in CVID patients than in the general population. We initiated this study to evaluate lung functions and identify risk factors for BA and bronchial hyperresponsiveness (BHR) in patients with CVID. METHODS: Twenty-three patients with CVID were included in this study. In all of them, spirometry and a metacholine bronchoprovocation test were performed. We also investigated the role of atopy, eosinophilic inflammation, and potential risk factors such as gender, age, or immunoglobulin levels at the time of diagnosis. RESULTS: BHR was confirmed in 12 patients (52%), all of whom had normal FEV1 and FEV1/FVC. However, BHR-positive patients had significantly decreased MEF25. BHR-positive patients had also more symptoms related to bronchial obstruction, with 8 of them (35%) being suspected of having BA at the end of the study. A higher prevalence of BHR was found in females, with a relative risk of 2.89. CONCLUSIONS: An increased prevalence of BHR and BA was detected in CVID patients compared to the general population. BA may develop despite the disturbed immunoglobulin production, and the majority of patients display nonatopic and noneosinophilic properties. These results suggest a limited role of atopy and eosinophilic inflammation in the pathogenesis of BA in CVID patients.
Keywords: průzkumy a dotazníky; Female; Phenotype; biologické markery; imunoglobulin G; Biomarkers; bronchiální hyperreaktivita; ženské pohlaví; Surveys and Questionnaires; imunoglobulin M; běžná variabilní imunodeficience; lidé; bronchoprovokační testy; Asthma; Immunoglobulin G; Risk Factors; Common Variable Immunodeficiency; Male; Immunoglobulin M; bronchiální astma; Bronchial Provocation Tests; podskupiny lymfocytů; rizikové faktory; kožní testy; Respiratory Function Tests; Lymphocyte Subsets; fenotyp; mužské pohlaví; respirační funkční testy; Bronchial Hyperreactivity; Skin Tests; Humans